High Doses of Bupleurum falcatum Partially Prevents Estrogen Deficiency-Induced Bone Loss With Anti-osteoclastogenic Activity Due to Enhanced iNOS/NO Signaling - Yeom, Mijung; Kim, Eun-Young; Kim, Jae-Hyun; Jung, Hyuk-Sang; Sohn, Youngjoo (Frontiers in Pharmacology, 2018)
Background and Objective: Bupleurum falcatum (BF) extract, a natural product with anti-inflammatory properties, has been traditionally used to treat menopausal symptoms, but its role in osteoporosis, another serious health concern of menopausal women, remains unknown. Here we investigated whether and how BF prevents estrogen deficiency-induced bone loss using both in vitro and in vivo models. Methods: Female Sprague-Dawley rats were ovariectomized (OVX) and subjected to oral BF treatment daily for eight weeks. Additionally, pre-osteoclastic RAW 264.7 cells were employed to evaluate the effects of BF and its underlying mechanism on receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclast formation in vitro. Results: A high dose of BF partially prevented ovariectomy (OVX)-induced bone loss and reduced the levels of tartrate-resistant acid phosphatase (TRAP) in serum and osteoclast numbers in femurs of OVX rats. Furthermore, BF clearly inhibited RANKL-induced osteoclast differentiation and bone resorption activity in RAW 264.7 cells. BF also inhibited the osteoclastogenic transcription factors c-Fos and nuclear factor of activated T cells c1 (NFATc1) and, consequently, downregulated the expression of osteoclast marker genes. Moreover, BF upregulated interferon-β (IFN-β)/inducible nitric oxide synthase (iNOS)/nitric oxide (NO) signaling, even though it had no impact on mitogen-activated protein kinases or NF-B. The inhibition of osteoclast formation by BF was abrogated by iNOS-specific inhibitors. Consistent with cellular studies, BF upregulated iNOS protein expression in femurs from OVX rats. Conclusion: Taken together, our results indicate that BF partially prevented estrogen deficiency-induced bone loss with anti-osteoclastogenic activity potentially due to enhanced iNOS/NO signaling.